Electrochemically assisted photocatalysis: Highly efficient treatment using thermal titanium oxides doped and non-doped electrodes for water disinfection - dos Santos, Andreia Betina Kreuser [UNESP]; Claro, Elis Marina Turini [UNESP]; Montagnolli, Renato Nallin [UNESP]; Cruz, Jaqueline Matos [UNESP]; Lopes, Paulo Renato Matos [UNESP]; Bidoia, Ederio Dino [UNESP] (Elsevier, 2017)
Electrochemically assisted photocatalysis (by electronic drainage) is a highly promising method for disinfection of water. In this research, the efficiency of photolytic oxidation using UV-A radiation and electrochemically assisted photocatalysis (with electric potential of 1.5 V) was studied by using electrodes prepared by thermal treatment and doped with silver, for inactivation of Escherichia coli and Staphylococcus aureus. The Chick-Watson microorganism inactivation model was applied and the electrical energy consumption of the process was calculated. It was observed no significant inactivation of microorganisms when UV-A light or electric potential were applied separately. However, the electrochemically assisted photocatalytic process, with Ag-doped electrode completely inactivated the microbial population after 10 (E. coli) and 60 min (S. aureus). The best performing non-doped electrodes achieved 52.74% (E. coli) and 44.09% (S. aureus) inactivation rates after 60 min. Thus, electrochemically assisted photocatalytic activity was not only effective for the inactivation of microorganisms, but also notably low on electrical energy consumption during the treatment due to small current and low electric potential applied.
Keywords: Ag-doped electrodes; Bacterial inactivation; Electron drainage; Kinetics study; Thermal oxides